Endoscopic self‐expandable metallic stenting for palliation of malignant gastric outlet obstruction in Southeast Asia. Issue 6 (7th October 2014) - Lye, Tiffany Jian Ying; Goh, Yaw Chong; Eng, Alvin Kim Hock; Ong, Hock Soo; Wong, Wai Keong; Chan, Weng Hoong
Abstract: Background: Malignant gastric outlet obstruction (GOO) is a pre‐terminal event in the natural history of gastric and pancreaticobiliary cancers. The use of endoscopic placement of self‐expandable metallic stents (SEMS) is a less invasive alternative palliative option for these patients. This is the first study in Southeast Asia to evaluate the clinical efficacy and safety of endoscopic SEMS placement in patients with malignant GOO. Methods: A retrospective review of our department's database in endoscopic SEMS placement for the treatment of malignant GOO was performed. Twenty‐four patients with advanced or metastatic malignancy that underwent placement of SEMS for treatment of malignant GOO between January 2003 and July 2013 were analysed. The GOO severity score was used as an objective means of assessing patients' oral intake. Results: Technical success rate was 100%. All patients resumed oral intake of liquids within the same day of stent placement. Clinical success was achieved in 21 patients (87.5%). There was a significant improvement of GOO severity score from 0.62 ± 1.0 (mean ± standard deviation) before stent placement to 2.04 ± 0.86 after stent placement ( P < 0.001). Complication rate was 12.5%. Stent‐related complications observed include stent migration (two patients) and tumour ingrowth (one patient). Serious complications such as gastrointestinal haemorrhage or perforation did not occur in any patients. The median survival after stent placement was 57 days (95% confidence interval, 12.2–101.8 days). None of the patients died from stent‐related complications. Conclusion: Endoscopic SEMS placement is a minimally invasive, safe and effective option for the palliation of malignant GOO.